Development of a Nanostructured Lipid Carrier (NLC) by a Low-Energy Method, Comparison of Release Kinetics and Molecular Dynamics Simulation - Andrea C. Ortiz; Osvaldo Yañez; Edison Salas-Huenuleo; Javier O. Morales (MDPI AG, 2021)
Lipid nanocarriers have a great potential for improving the physicochemical characteristics and behavior of poorly water-soluble drugs, such as aqueous dispersibility and oral bioavailability. This investigation presents a novel nanostructured lipid carrier (NLC) based on a mixture of solid lipid glycerides, fatty acid esters of PEG 1500 (Gelucire® 44/14), and an oil mix composed of capric and caprylic triglycerides (Miglyol® 812). These NLCs were developed by a simple low-energy method based on melt emulsification to yield highly encapsulating and narrowly distributed nanoparticles (~100 nm, PdI = 0.1, and zeta potential = ~−10 mV). Rhodamine 123 was selected as a poorly water-soluble drug model and owing to its spectroscopic properties. The novel NLCs were characterized by dynamic light scattering (DLS), zeta potential, nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and colloidal stability. The drug release was determined through a dialysis bag and vertical Franzs' cells to provide insights about the methods' suitability, revealing similar performance regardless of their different fluid dynamics. Rhodamine 123 followed a characteristic biphasic release profile owing to the swelling of the hydrophilic polymer coating and diffusion process from the lipid core as revealed by the Korsmeyers-Peppas kinetic modeling. Moreover, to elucidate the formation and incorporation of Rhodamine 123 into the NLC core, several molecular dynamics simulations were conducted. The temperature was shown to be an important condition to improve the formation of the nanoparticles. In addition, the liquid lipid incorporation to the formulation forms nanoparticles with imperfect centers, in contrast to nanoparticles without it. Moreover, Miglyol® 812 improves hydrophobic molecule solubility. These results suggest the potential of novel NLC as a drug delivery system for poorly water-soluble drugs.